Research on the Optimal Allocation of Human Resources based on Business Administration - Xu, Hai (International Journal of Social Sciences and Public Administration, 2025)
From the perspective of business administration, this paper conducts an in-depth exploration of the optimal allocation of human resources, briefly describes the connotation and development process of business administration, defines the optimal allocation of human resources, and expounds the application principles of business administration in the allocation of human resources. In a highly competitive business environment, companies need to elevate the rational allocation of human resources to a strategic level. Through the forecasting of human resource demand, the analysis of human resource supply and the analysis and evaluation of positions, we can help enterprises accurately grasp the supply and demand of human resources, scientifically allocate positions, release potential, and improve operational efficiency and competitiveness. Through a detailed analysis of Tencent's optimal allocation of human resources, we found that there were problems and put forward improvement strategies, so as to provide a scientific and effective reference framework and guiding principles for enterprises to improve human resource allocation, so as to help enterprises stand out from the competition and achieve stable and sustainable development.